Development of Interactive E-LKPD Liveworksheet Based on Contextual Teaching and Learning (CTL) on Biodiversity Materials as Student Teaching Materials - Fauziyah, G.H; Juanda, Anda; Gloria, R.Y. (Technium Education and Humanities, 2025)
The development of teaching materials in the form of E-LKPD was motivated by the limitations of teaching materials used at SMAN 1 Beber. This study aims to produce interactive e-LKPD-based biodiversity liveworksheets (CTL) as valid and practical teaching materials for class X students. This research uses the (R&D) method. The instruments used are needs analysis instruments, validation sheets for material experts and media experts, and questionnaires for teacher and student responses. The feasibility results of the E-LKPD based on the assessment of material experts reached a value of 0.60 with the criteria of "High" validity level and media experts gave an assessment of 0.93 with the criteria of "Very High" validity level. The result of the product trial based on responses from educators was 92.42% "Very Feasible". According to the questionnaire, the student response showed a score of 77% with the criteria of "Feasible". This shows that E-LKPD meets the criteria of being very valid, very practical and suitable for use in learning by teachers and students.